A CASE OF MIGRAINE WITH SYMPTOMS OF PERCEPTION DISORDERS INCLUDING A FAMILY HISTORY. Issue 2 (4th March 2022) - Tanrıverdi, Çiğdem; Kara, İhsan
ABSTRACT: Alice in Wonderland Syndrome is characterized by distortions in perception, especially with signs of micropsia or macropsia, peropia, teleopsia.The etiology of this syndrome includes migraine attacks, epilepsy, infections or substance abuse.In this case study, a 15-year-old adolescent girl was admitted to our child and adolescent psychiatry clinic with complaints of seeing objects and people as larger or smaller than they are and/or perceiving objects closer or farther than they are, before her migraine attacks.It was also stated that his father had similar complaints during his adolescence..In this case report, we present a case of migraine with aura.